PARTISIPASI PETANI DALAM PROGRAM PENGEMBANGAN JAGUNG HIBRIDA (Suatu Kasus pada Kelompoktani di Desa Mulyasari Kecamatan Mande Kabupaten Cianjur) - Muthiara Hasna; Dika Supyandi (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Corn is a multipurpose commodity, the demand for corn needs especially as a raw material for animal feed continues to increase. In 2015, the Ministry of Agriculture made a breakthrough to achieve self-sufficiency in corn and make Indonesia as the world of corn granary in the future. The government developed hybrid corn to every area that had development potential including Cianjur Regency. Mande Subdistrict is one of the districts with quite large corn production and there are company that produce animal feed where its existence was a form of cooperation between the Ministry of Agriculture and the Association of Animal Feed Companies (GPMT) as an effort to absorb local corn. This study aimed to explain the level of farmer participation, determine the type of participation which provided by farmers in the hybrid corn development program. The sample in this study used simple random sampling technique with a sample of 82 respondents. The design used quantitative design with survey method. Data analysis used descriptive statistics with the scoring. The results showed that the level of farmer participation in the hybrid corn development program was in the good category. The types of participation provided by farmers are in the form of energy, thoughts, skills, goods and money.